LEGAL ASPECTS OF REGISTRATION AS A MEANS OF PUBLIC ADMINISTRATION IN THE FIELD OF GENERAL SECONDARY EDUCATION - Zhukova, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to study the legal aspects of registration as a means of public administration in the field of general secondary education by forming key challenges facing the state process in maintaining the appropriate quality of education for general secondary education applicants. Results: determines that in modern conditions, the registration procedure as a means of public administration in the field of general secondary education ensures transparency, openness and efficiency of management processes in this field. It has been proven that the key purpose of the registration procedure of institutions of general secondary education can be considered to be the control and supervision of the activities of institutions of general secondary education, the direction and coordination of the national education system (including the field of general secondary education as a systemic element of the educational space) and guaranteeing the provision of quality educational services in institutions general secondary education. It is noted that with the help of the registration procedure as a means of public administration in the field of general secondary education, the state is able to make sound management decisions regarding institutions of general secondary education. At the same time, indicators of the potential of scientific and pedagogical workers and the educational policy implemented by a certain educational institution are taken into account. It is substantiated that the registration procedure belongs to the process of granting legal permission for the activities of educational institutions, as well as to the process of checking the competence of applicants and providers of educational services, which is evidence of the complex nature of the said process. Registration as a means of public administration in the field of general secondary education, therefore, aims at the sectoral development of the specified field with an emphasis on improving the competence of its participants. It has been analyzed that from a legal point of view, at the same time, under such conditions, the context of the combination of goals for each of the specified segments remains unclear: general (general secondary education as a regulatory and administrative construct) and special (providers and recipients of educational services in the field of general secondary education). Discussion: it would be expedient to consider the phenomenon of the registration procedure as a means of public administration in the field of general secondary education, first of all, from the position of directing and coordinating with its help other branches related to this process, which are its constituent parts (scientific and pedagogical employees, recipients of educational services).